Interweaving globalisation and growth: A causal exploration across income levels - Irushi Sandanayaka; Danushi Rathnayake; Dinithi Athalage; Piyara Wijesuriya; Ruwan Jayathilaka (Social Sciences and Humanities Open)
Economic growth is a crucial global macroeconomic goal and globalisation is widely regarded as a key driver of growth in today's interconnected world. However, previous studies have largely examined this relationship in a generalised manner, often without allocating equal focus to the multiple dimensions of globalisation. This study explores the causal relationship between economic growth and globalisation—encompassing its economic, social, and political dimensions—across 97 countries grouped by income level. The analysis spans 51 years (1971–2021) and employed the Panel Granger Causality Test. Unlike most existing studies, which primarily focus on global and country-level trends, the current findings disclose a bidirectional relationship between economic growth and globalisation in both high and low-income groups. The results also reveal a growth driven globalisation in the upper-middle-income group, and a globalisation-driven growth in the lower-middle income group. Accordingly, policy recommendations are formulated in alignment with the Sustainable Development Goals (SDGs) set by the United Nations and tailored to income specific contexts to assist stakeholders in drafting effective and personalised strategies. These include promoting sustainable production practices and technology transfers in low-income nations, enhancing policies to support international trade in the lower-middle-income group, investing in human capital development in upper-middle-income nations, and encouraging technological advancements in high-income nations. This study contributes to the empirical literature on the globalisation-growth nexus across income classifications, offering intricate and timely insights spanning a fifty-year timeframe.